Inovasi Pembelajaran Mata Pelajaran SKI Kelas VI - Rohmat, Rohmat (Journal of Comprehensive Science, 2025)
The phenomenon of education in Indonesia shows a decline in basic moral and ethical values, so the role of teachers as innovative role models is very crucial. Since the enactment of the 2013 Curriculum, the challenges in implementing integrative thematic education have demanded a change in the mindset of teachers to produce superior and characterful students. The purpose of this study is to examine innovative learning models in SKI class VI subjects in order to optimize the role of teachers as role models and improve the quality of education. This study also analyzes the effectiveness of interactive learning strategies in shaping students' character and creativity. The methods used include literature study and descriptive analysis by reviewing books, journals, and educational regulations to understand the application of learning innovations. The study considers a variety of models, such as problem-based, contextual, and cooperative learning, to provide a comprehensive picture of innovative learning practices. The results of the study show that the application of innovative models increases students' creativity, collaboration, and activeness in the learning process. Teachers who implement interactive strategies are proven to be able to form a professional attitude and strong character in students. The conclusion of the study confirms that teacher integrity and exemplary behavior are the main keys in creating an effective learning environment. Strengthening the values of justice, truth, and hard work in teaching is expected to produce the next generation of intellectual, emotional, and spiritual qualities.